Constructing durable carbon layer on LiMn0.8Fe0.2PO4 with superior long-term cycling performance for lithium-ion battery. (10th February 2016) - Yang, Liangtao; Xia, Yonggao; Fan, Xu; Qin, Laifen; Qiu, Bao; Liu, Zhaoping
Graphical abstract: Highlights: The durable carbon layer is constructed by CVD coating method, successfully. Mn dissolution of treated cathode material is effectively suppressed. Long-term cycling performance of the treated cathode material is improved. The rate capability of the treated material is enhanced. Abstract: LiMn0.8 Fe0.2 PO4 is becoming one of the most promising cathode materials for lithium ion batteries. However, the capacity suffers from a loss during long-term cycling, which is directly associated with Mn dissolution due to the disproportionation reaction of Mn 3+ . Here, we report a chemical vapor deposition (CVD) approach to modify LiMn0.8 Fe0.2 PO4 particles with carbon so as to minimize Mn dissolution from cathode. The deposited carbon layer not only protects LiMn0.8 Fe0.2 PO4 cathode from electrolyte corrosion, but also enhances the electronic/ionic conductivity owing to its higher graphitize degree. As a consequence, the electrochemical performances have a significant improvement. The capacity retention achieves 96% after 450 cycles at 1 C at room temperature (25 °C). Even at elevated temperature (55 °C), the capacity retention also reaches at 97 % after 50 cycles at 1 C rate, which is much higher than that of untreated sample (89%). Hence, the cathode material based on LiMn0.8 Fe0.2 PO4 encapsulated with durable carbon by CVD method represents a promising strategy for developing its long-term cycling performance through suppressing Manganese dissolution.